Properties of a new hemostatic gauze prepared with in situ thrombin induction. (4th January 2017) - Liu, Jiawei; Lan, Guangqian; Lu, Bitao; He, Liwei; Yu, Kun; Chen, Jinghao; Wang, Tao; Dai, Fangying; Wu, Dayang
Abstract: The aim of this study was to develop a new safe and effective hemostatic gauze material by promoting in situ thrombin induction on the surface of gauze, and the optimal preparation conditions were determined by varying the CaCl2 concentration, reaction time, and temperature. Under each condition, the thrombin amount (optical density) and plasma clotting time were measured, and the results showed that the best condition for preparation of this new gauze/plasma composite (GP) is a CaCl2 concentration of 0.08 mol l −1 at 35 °C for 2.5 h. Temporal and water stability tests showed that the gauze is washable and can be stored without loss of quality. Furthermore, the water and blood absorption and whole blood clotting time were compared between the GP and oxidized cellulose (OC), demonstrating that the hemostatic effect of the new material was similar to that of OC; however, the thermophysical stability of GP was superior to that of OC. The good hemostatic effect of the new hemostatic gauze was verified in a rabbit artery bleeding model, which is considered to be due to the presence of thrombin on its surface. These results are expected to provide important guidance in the continued search for new types of hemostatic gauze.